Charge‐Induced Structural Changes of Confined Copolymer Hydrogels for Controlled Surface Morphology, Rheological Response, Adhesion, and Friction. (10th December 2021) - Deptula, Alexander; Wade, Matthew; Rogers, Simon A.; Espinosa‐Marzal, Rosa M.
Abstract: The ability to modulate polyacrylamide hydrogel surface morphology, rheological properties, adhesion and frictional response is demonstrated by combining acrylic acid copolymerization and network confinement via grafting to a surface. Specifically, atomic force microscopy imaging reveals both micellar and lamellar microphase separations in grafted copolymer hydrogels. Bulk characterization is conducted to reveal the mechanisms underlying microstructural changes and ordering of the polymer network, supporting that they stem from the balance between hydrogen bonding in the substrate‐grafted hydrogels, electrostatic interactions, and a decrease in osmotically active charges. The morphological modulation has direct impacts on the spatial distribution of surface stiffness and adhesion. Furthermore, lateral force measurements show that the microphase separations lead to speed and load‐dependent lubrication regimes as well as spatial variation of friction. A proof of concept via salt screening demonstrates the dynamic control of surface morphology and adhesion. This work advances the knowledge necessary to design complex hydrogel interfaces that enable spatial and dynamic control of surface morphology and thereby of friction and adhesion through modulation of hydrogel composition and surface confinement, which is of significance for applications in biomedical devices, soft tissue design, soft robotics, and other engineered tribosystems. Abstract : This works shows how varying the charge density distribution in hydrogels via copolymer composition and network confinement is a means to modulate (micellar and lamellar) surface morphology and hydrogel strengthening. The surface morphology has a direct influence on the spatial variation of stiffness, friction, and adhesion. Further, the responsiveness of the surface morphology and adhesion to chemical stimulation is demonstrated.